The function of the adductors and iliopsoas during the maximal running velocity phase of sprinting - Ohshima, Y.; Fujii, N. (Japan Journal of Physical Education, Health and Sport Sciences, 2017)
The purpose of this study was (1) to quantify the contribution of the adductors and iliopsoas to the hip joint torque, and (2) to clarify the function of the adductors and iliopsoas for terminal support until early recovery in maximal velocity sprinting. Eight male track and field athletes volunteered for the present study, and sprinted 60 m from a standing start position. Ground reaction force to the right leg was measured using a force platform (1000 Hz) placed at the 50-m mark from the start position. Simultaneously, 3-dimensional coordinates of body landmarks were recorded by a motion capture system (250 Hz) with 20 cameras. The right hip joint torque was calculated using inverse dynamics. To estimate the muscle forces of the right lower limb, we created a musculoskeletal model. The contribution of the muscle forces to the right hip joint force was calculated based on both equations of motion for each segment and equations of constraint conditions for adjacent segments connected by a joint. The main results for terminal support until early recovery were: (1) The adductor muscles generated less torque during hip joint flexion. (2) These muscles were involved in forward acceleration of the leg on the same side. (3) The iliopsoas was involved in the forward swing of the thigh on the same side. Based on these results, it can be concluded that the hip adductors do not function as hip flexors, but as forward accelerators of the leg on the same side, based on the hip joint adductor torque. In contrast, the iliopsoas does not function as a forward accelerators of the leg on the same side, but delivers forward swing to the thigh on the same side for hip joint flexion torque.